Estimating the amount of information carried by a neuronal population - Yu, Yunguo; Crumiller, Marshall; Knight, Bruce; Kaplan, Ehud (Frontiers in Computational Neuroscience, 2010)
Although all brain functions require coordinated activity of many neurons, it has been difficult to estimate the amount of information carried by a population of spiking neurons. We present here a Fourier-based method for estimating the information delivery rate from a population of neurons, which allows us to measure the redundancy of information within and between functional neuronal classes. We illustrate the use of the method on some artificial spike trains and on simultaneous recordings from a small population of neurons from the lateral geniculate nucleus of an anesthetized macaque monkey.